A new genus of Iassinae (Hemiptera: Cicadellidae) from Peru and a new species of Daveyoungana Blocker & Webb - Dai, Wu; Dietrich, Christopher H. (Zootaxa, 2015)
The new iassine leafhopper genus Linnavuoria is described and illustrated based on L. tingomariaensis sp. nov., from Peru, and placed in the previously monobasic tribe Selenomorphini (based on Selenomorphus Evans from New Caledonia), along with two other New World genera, Pachyopsis Uhler and Scaroidana Osborn (new placements). The new genus is similar to Pachyopsis in overall structure, but differs as follows: head with crown flat and forming distinct angle with face in profile; face coarsely punctate, without distinct transverse striations or rugae; lateral frontal sutures extended from antennal ledge to midline and joining with distinct coronal suture; forewing with numerous dark pigment spots corresponding to setal sockets; hind femur with macrosetal formula 2+1+1+1. A revised diagnosis and key to genera are given for Selenomorphini. The previously monotypic leafhopper genus Daveyoungana Blocker & Webb (Iassinae: Hyalojassini) recorded from Brazil is also reviewed and the detailed morphology of the genus is redescribed and illustrated, including the first description of the female. A new species, D. maniforma sp. nov. from Ecuador is described and illustrated and a key to the species in this genus is given.